Injury Incidence and Prevalence in New Zealand High Performance Sports - Sayer, Jennifer Lorraine (Auckland University of Technology, 2017)
Introduction. Injury surveillance data is required to determine injury incidence and prevalence within different sporting codes. This allows injury prevention strategies to be targeted to the specific sports. High Performance Sport New Zealand (HPSNZ) has developed an injury surveillance system, part of which includes an online app, to monitor injuries within sports but its effectiveness has not yet been determined. Purpose. To determine the injury incidence and prevalence in HPSNZ sports Methods. One hundred and fifteen New Zealand carded athletes across the five sporting disciplines of men’s hockey, women’s hockey, women’s football, kayaking and sailing completed a longitudinal prospective cohort study over twelve months. The sample was made up of 45 males (mean age 24.22 SD. 3.97) and 71 females (mean age 22.96 SD. 4.15) with data collected weekly using the HPSNZ “Programme for Injury and Illness Surveillance” (PILLS) self-reported injury surveillance app. Results. The overall compliance rate was 60.63%. Injury incidence across the entire sample was 10.67/ 1000 athlete exposures (AE). The injury incidence for the five sports was as follows: men’s hockey 14.15/1000 AE; women’s hockey 13.38/1000 AE; women’s football 8.18/1000 AE, kayaking 4.35/1000 AE and sailing 5.59/1000 AE. Injury prevalence for the five sports was; 2.72 for men’s hockey, 4.26 for women’s hockey, 2.48 for women’s football, 1.07 for kayaking and 1.33 for sailing. Seventy-five percent of the entire sample experienced at least one time loss injury during the study duration. Conclusion. Training injury incidence and prevalence was reported for five HPSNZ sports. The team sports had higher injury incidence and prevalence rates than both kayaking and sailing. The PILLS app allowed for training exposure estimates to be made however it requires further development, or needs to be used in conjunction with other monitoring systems, in order to capture all relevant injury data and competition exposure. It is suggested that exposure measures need to be captured using alternative methods rather than through the injury surveillance tool.
Keywords: Injury; Incidence; Prevalence; Sport